The Influence of Characteristics of Worker and Business on the Income of Informal Sector Workers in Yogyakarta - Jagad Hidayat Jati; Sri Rum Giyarsih; Luthfi Muta'ali (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
Yogyakarta has excellent human resources, but informal sector workers are threatened with low income. This article aims to examine how the influence of worker and business characteristics on informal sector workers’ income in Yogyakarta. Characteristic of workers consist of education, work or business experience, status in the household, marital status, gender, and age. Then business characteristics consist of types of business fields, working days, hours of work, length of work, use of internet technology, and financial bookkeeping. The study was conducted quantitatively using secondary data sources obtained from the National Labor Force Survey (Sakernas) in August 2018. The data were analyzed using binary logistic regression. The findings show that both partially and simultaneously, each factor of the two characteristics has a significant influence on the income of informal sector workers in Yogyakarta.